2007
DOI: 10.5194/angeo-25-915-2007
|View full text |Cite
|
Sign up to set email alerts
|

Spatial scaling of optical fluctuations during substorm-time aurora

Abstract: Abstract.A study of statistical features of auroras during substorm activity is presented, emphasizing characteristics which are commonly applied to turbulent flows. Data from all-sky television (TV) observations from the Barentsburg observatory (Svalbard) have been used. Features of the probability density function (PDF) of auroral fluctuations have been examined at different spatial scales. We find that the observed PDFs generally have a non-Gaussian, heavy-tailed shape. The generalized structure function (G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
12
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 28 publications
3
12
0
Order By: Relevance
“…This was previously reported by Kozelov and Rypdal (2007) by TV allsky observations. For larger spatial scales observed by the Polar UVI imager, a similar temporal variation of the roughness exponent of self-affine auroral surfaces was reported by Uritsky et al (2006).…”
Section: Introductionsupporting
confidence: 77%
See 2 more Smart Citations
“…This was previously reported by Kozelov and Rypdal (2007) by TV allsky observations. For larger spatial scales observed by the Polar UVI imager, a similar temporal variation of the roughness exponent of self-affine auroral surfaces was reported by Uritsky et al (2006).…”
Section: Introductionsupporting
confidence: 77%
“…2 above and in the previous studies (e.g. Uritsky et al, 2006;Kozelov and Rypdal, 2007), we conclude that the involved non-linear interactions between scales indicate an inverse energy cascade. In our study this is shown from examining time evolution of scaling index α A of auroral fluctuations at the beginning of substorm expansion by Polar imaging observations.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…There are many problems that remain open for future consideration. In particular, the assumption regarding the classical geometry (d = 2) of small-scale emission regions will need to be verified, especially for the range L < 100 km where fractal behavior of substorm time optical aurora has been documented [Kozelov and Rypdal, 2007]. The isotropic a is another ad hoc assumption requiring additional data validation and adjustment.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to statistical approaches dealing with individual auroral images Kozelov and Rypdal, 2007), our study involved spatiotemporal tracking of emission events as briefly explained below. In most cases, this tracking made it possible to identify the precipitation events that co-evolved simultaneously in multiple auroral locations and could not be resolved otherwise (Uritsky et al, 2002).…”
Section: Detection Of Spatiotemporal Eventsmentioning
confidence: 99%